Assessing the potential of de-oiled peanut (Arachis hypogea) seeds for surface water treatment: A sustainable alternative to chemical coagulants - Raed S. Al-Wasify; Shimaa R. Hamed; Samar Ragab (Egyptian Journal of Aquatic Research, 2023)
Since natural coagulants are readily available, inexpensive, nontoxic, and biodegradable, they are now proving to be effective alternatives to chemical coagulants. This research article investigates the potential of de-oiled peanut (Arachis hypogaea) seeds as a natural coagulant for surface water treatment, comparing its effectiveness with alum, a widely-used chemical coagulant. Ten surface water samples were obtained from the Nile River in the greater Cairo region and treated using coagulants – peanut seeds and alum. Key parameters, such as turbidity, chemical oxygen demand (COD), total bacterial count (TBC), Escherichia coli, and enterococci, were measured to assess the coagulation efficiencies of both substances. Results revealed a minor disparity in turbidity removal, with peanut seeds achieving 75.4% to 85.0% removal, while alum exceeded 90.0%. A more pronounced difference in COD removal was observed, as peanut seeds exhibited a 41.7–53.2% removal rate, in contrast to alum’s maximum removal of 92.3%. Regarding bacterial removal efficiency, alum demonstrated a slightly superior performance (60.0–70.0%) compared to peanut seeds (approximately 50.0%). In conclusion, de-oiled peanut seeds represent an affordable and environmentally friendly alternative coagulant for surface water treatment.